Dipole-Dipole Interaction Model for Oriented Aggregation of BaTiO3 Nanocrystals. Issue 1663 (13th March 2014) - Yasui, Kyuichi; Kato, Kazumi
ABSTRACT: In order to study the oriented aggregation of BaTiO3 nanocrystals in the ultrasound-assisted synthesis in an aqueous solution [F.Dang et al., Jpn.J.Appl.Phys. 48, 09KC02 (2009)], the electric dipole-dipole interaction model has been studied by numerical simulations. The results of the numerical simulations are consistent with the experimental ones if the electric dipole moment of a primary particle (a nanocrystal) of 5 nm in diameter is about 10 D =3.3 x 10 -29 (C m). It suggests that a 5-10 nm BaTiO3 nanocrystal synthesized in an aqueous solution with ultrasound has spontaneous polarization.